STRATEGI KOMUNIKASI POLITIK KPUD LOMBOK UTARA DALAM MENINGKATKAN PARTISIPASI PEMILIH PADA PEMILU 2024 - Fathurrijal Fathurrijal; Ishanan Ishanan; Yusron Yusron; Suhadah Suhadah (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
The North Lombok Regional General Election Commission (KPUD) is a state institution that regulates the implementation of democratic contestation at the regional level of North Lombok, West Nusa Tenggara Province. One of the main functions of the regional KPU is to carry out political communication activities to socialize the stages of the General Election (Election) to the public so that people's political participation increases. This study examines how the political communication strategy carried out by The North Lombok Regional General Election Commission (KPUD), from the aspects of Process, planning, messages, political communication media and community participation. This study uses a qualitative descriptive approach, research data is obtained from various sources. The results of this study show that the process, planning, messaging, and political communication media of The North Lombok Regional General Election Commission (KPUD) in the 2024 election are carried out through political education, the use of cultural facilities, watching tancap screen movies together, through collection and counting simulations at TPS Real. Through the cooperation of local mass media, and the KPU Goes To School program. All of these activities are to awaken, and foster public awareness to go to the Polling Station (TPS).